The Effect of Financial Literacy, Income and Financial Attitudes on Family Financial Management for Low Income People - Natalia Sigo Kumanireng; Haryati Setyorini (PT FORMOSA CENDEKIA GLOBAL, 2022)
The importance of education, especially in increasing understanding of finance for the community, is very important to do. Knowledge of financial management is very important, especially in managing and also managing family finances, especially for people who live in Lembata Regency (Flores-NTT). The purpose of this study is to find out how financial literacy skills are for the people of Lembata Regency. In this study, researchers used a sample of people living in the Lembata Regency (Flores-NTT). The sampling technique used in this study was purposive sampling, then data collection was carried out online using Google Forms by adjusting to the research criteria so that researchers used 100 respondents, and used wrap PLS to test research instruments and analysis. The results of this study indicate that financial literacy has a significant positive effect on family financial management, income has a significant positive effect on family financial management and financial attitude has a significant positive effect on family financial management.